Enzyme-catalyzed acylation of (R,S)-1-phenylethanol in 1-butyl-3-methylimidazolium based ionic liquids - Paljevac, Muzafera; Knez, Željko; Leitgeb, Maja (Slovensko kemijsko društvo, 2012)
Ionic liquids represent an exciting new class of reaction solvents for catalysis, which have been used successfully for enzyme-catalyzed reactions. In present research, three different ionic liquids, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium hexafluorophosphate, and 1-ethyl-3-methylimidazolium bis[(trifluoromethyl)sulfonyl)] amide, were synthesized. They were used as a reaction medium for enzyme-catalyzed acylation of (R,S)-1- phenylethanol with vinyl acetate. Mentioned enzymatic reaction was performed in a batch stirred-tank reactor in order to optimise different reaction parameters (biocatalyst concentration, temperature, .). The influence of three different immobilized lipases on reaction performance was studied as well. The highest reaction rate and conversion of 49.7% after 5 h of reaction performance was achieved in the case when immobilized lipase Novozym 435 from Candida antarctica was used as a biocatalyst and hydrophilic ionic liquid 1-butyl- 3-methylimidazolium tetrafluoroborate as a solvent. Therefore, the optimization of different reaction parameters on lipase- catalyzed acylation of (R,S)-1-phenylethanol was carried out in 1-butyl-3-methylimidazolium tetrafluoroborate. Ionske tekočine predstavljajo zanimiv razred reakcijskih topil za katalizo, ki se uspešno uporabljajo za encimsko katalizirane reakcije. V našem delu smo sintetizirali tri različne ionske tekočine, in sicer 1-butil-3-metilimidazolijev tetrafluoroborat, 1-butil-3-metilimidazolijev heksafluorofosfat in 1-etil-3-metilimidazolijev bis[(trifluorometil)sulfonil)]amid, z namenom, da določimo najprimernejšo ionsko tekočino kot topilo za encimsko katalizirano acilacijo (R,S)-1-feniletanola z vinil acetatom in za optimizacijo reakcijskih parametrov (koncentracije biokatalizatorja, temperature, .) za omenjeno reakcijo, ki smo jo izvedli v mešalnem šaržnem reaktorju. Proučili smo tudi vpliv treh različnih imobiliziranih lipaz na potek reakcije acilacije. Najvišjo začetno hitrost reakcije in 49.7% presnovo po 5 h reakcije smo dosegli, ko smo kot biokatalizator uporabili imobilizirano lipazo Novozym 435 iz Candida antarctica in hidrofilno ionsko tekočino 1-butil-3-metilimidazolijev tetrafluoroborat kot reakcijski medij. Tako smo vpliv reakcijskih parametrov, kot so koncentracija biokatalizatorja, temperatura in koncentracija substratov, na acilacijo (R,S)-1-feniletanola, optimirali v 1-butil-3-metilimidazolijevem tetrafluoroboratu.